Helium CT: Monte Carlo simulation results for an ideal source and detector with comparison to proton CT - Piersimoni, Pierluigi; Volz, Lennart; Seco, Joao (Medical physics, 2018)
Purpose - To evaluate the accuracy of relative stopping power and spatial resolution of images reconstructed with simulated helium CT (HeCT) in comparison to proton CT (pCT). - - Methods - A Monte Carlo (...
Gesehen am 23.04.2020